Interleukins-1 and -6 stimulate the release of corticotropin-releasing hormone-41 from rat hypothalamus in vitro via the eicosanoid cyclooxygenase pathway. - Navarra, P; Tsagarakis, S; Faria, MS; Rees, L; Besser, G; Grossman, A (1991)
It has previously been shown that interleukin-1 (IL-1) directly stimulates the release of CRH-41 from rat hypothalamus in vitro, suggesting that cytokines may mediate the effects of changes in immune state on the hypothalamo-pituitary adrenal axis (HPA). However, it is likely that several cytokines can cause changes in neuroendocrine function, and we have now investigated a series of others for central activity on the HPA: IL-2, IL-6, IL-8, tumor necrosis factor (cachectin), interferon-alpha 2, and interferon-gamma. The static rat hypothalamic incubation system used involves fresh hypothalamic explants with consecutive 20-min incubation, and estimation of CRH-41 concentrations in the medium by a specific RIA; the acute effects of cytokines on ACTH release from rat dispersed pituitary cells were also measured. IL-6 increased hypothalamic CRH-41 secretion in the range 10-100 U/ml, but had no effect on isolated median eminences incubated in vitro under the same conditions. IL-6 (1-1000 U/ml) also had no effect on the secretion of ACTH from freshly dispersed rat anterior pituitary cells when administered in 10-min pulses. The effects of both IL-1 and IL-6 were antagonized by blockade of the eicosanoid cyclooxygenase pathway, but not by lipooxygenase blockade. Neither IL-2 (1-10000 U/ml), IL-8 (0.1-10 nM), tumor necrosis factor (10-1000 U/ml), interferon-alpha 2 (10-1000 U/ml) nor interferon-gamma (10-1000 U/ml) had any effect on hypothalamic CRH-41 release or pituitary ACTH release. It is therefore concluded that IL-6, like IL-1, can exert a potent enhancing effect on the HPA by acutely stimulating the secretion of CRH-41 from the hypothalamus at a site above the level of the median eminence, at concentrations known to occur in human plasma and cerebrospinal fluid. These effects are probably mediated by cyclooxygenase products. Acute stimulatory effects of the other cytokines investigated on the HPA are unlikely to be exerted through changes in either CRH-41 or ACTH directly.